‘Evolution of Species’ in Business: From Mice to Elephants. The Question of Small Enterprise Development - LITAU, Ekaterina (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
The aim of the present research was finding out why an overwhelming majority of small enterprises are incapable of growth. The paper provides a completely new view and explanation of the small and medium-sized enterprise development problem and presents the challenge-solving algorithm integrated into the web service for timely assessments facilitating a successful transition of enterprises into a group of big enterprises. The findings confirm that laws of the enterprise development are more universal than people commonly believe and not so dependent on external factors. The suggested concept of the informational challenge is a key development factor at small fast-growing enterprises managed by talented entrepreneurs. The concept helps to understand difficulties and cope with them in time of a business transition to the category of medium-sized enterprises. Long-term observations of 68 enterprises (longitudinal study) in Russia made it possible to identify preconditions for gazelle enterprises to appear and factors that prevent them from the sustained growth with an emphasized importance of some internal factors in these processes like entrepreneurs’ personality traits in particular.